GREEN SKYSCRAPER: A WAY TO SUSTAINABLE DEVELOPMENT - Riya Goyal (International Journal of Innovations in Engineering Research and Technology, 2021)
Green Skyscraper concept has emerged to mitigate the effects of the increasing impact on the environment and it can work as a smart solution to improve the building construction process. This paper presents the need of sustainable development especially in the developing countries like India. The provision of integrating plants into skyscraper includes the four possible options like Green Roof, Green Wall, Bio-filter and indoor potting plants which can be incorporated into the design. Green roof can reduce 50% of cooling load; Green wall can reduce 10% indoor temperature; whereas Bio-filter and internal plants purify air by 50-60%.